A successful pregnancy outcome in a known case of chronic kidney disease: a case report - Ray, Rituparna; Nayak, Vedavathy; S., Sreelatha; N., Hajira Sultana (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2025)
Chronic kidney disease (CKD) is defined as altered renal structure, function and morphology or glomerular filtration rate<60 ml/min for a minimum of 3 months. CKD affects approximately 6% women in reproductive age group in developed countries. The incidence is 0.03%-0.2% in pregnancy and if not diagnosed and treated on time, it may lead to poor prognosis. We are reporting a case of G2P1L1 at 24 weeks period of gestation with gestational hypertension, she was also a known case of CKD for 9 years not on treatment. She was followed up regularly with a multidisciplinary approach and successfully managed.